Postoperative analgesic requirements in patients exposed to positive intraoperative suggestions. - McLintock, T T (1990)
OBJECTIVE--To establish whether positive suggestions given to a patient under general anaesthesia reduce postoperative pain and analgesic requirements. DESIGN--Prospective double blind randomised study. SETTING--Operating theatre and gynaecology ward of a teaching hospital. PATIENTS--63 Woman undergoing elective abdominal hysterectomy were randomised to be played either a tape of positive suggestions or a blank tape during the operation through a personal stereo system. INTERVENTIONS--Three women were withdrawn from the study. Anaesthesia was standardised for all of the women. Postoperative analgesia was provided through a patient controlled analgesia system for the first 24 hours. Pain scores were recorded every six hours. MAIN OUTCOME MEASURES--Morphine consumption over the first 24 hours after the operation; pain scores. RESULTS--Mean morphine requirements were 51.0 mg (95% confidence interval 42.1 to 60.0 mg in the women played positive suggestions; and 65.7 mg (55.6 to 75.7 mg) in those played a blank tape. The point estimate (95% confidence interval) for the difference of means was 14.6 mg (22.4%) (1.9 (2.9%) to 27.3 mg (41.6%] (p = 0.028). Pain scores were similar in the two groups. CONCLUSION--Positive intraoperative suggestions seem to have a significant effect in reducing patients' morphine requirements in the early postoperative period.